Global Development of Research on Anorectal Malformations over the Last Five Decades: A Bibliometric Analysis - Illya Martynov; Xiaoyan Feng; Johannes W. Duess; Jan-Hendrik Gosemann; Martin Lacher; Steffi Mayer (MDPI AG, 2022)
Purpose: Anorectal malformations (ARM) are one of the most challenging congenital malformations in pediatric surgery. We aimed to assess the research activity on ARM over the last five decades. Methods: Data on original research publications were retrieved from the Web of Science Core Collection (1970-2020), and analyzed for countries, authors, scientific journals, and top-ten papers. Scientific quantity was assessed by the number of publications. Research quality was estimated from the number of citations, average citation rate per item (ACI), and h-index. Results: A total number of 1595 articles with 19,419 citations (ACI = 12.2; h-index = 54) were identified. The annual number of publications and citations significantly increased over time (p < 0.0001). The USA (n = 386; 24.2%), Japan (n = 153; 9.6%), and China (n = 137; 8.6%) were the most productive countries; and the USA (n = 7850; ACI = 20.3; h-index = 44), Japan (n = 1937; ACI = 12.6; h-index = 21), and the Netherlands (n = 1318; ACI = 17.3; h-index = 22) were the top cited countries. Articles were preferentially published in JPS (n = 391; 24.5%), PSI (n = 181; 11.3%), and EJPS (n = 56; 3.5%). Top-ten cited papers focused on classification (n = 1), surgical technique (n = 3), associated syndromes (n = 2), postoperative outcome (n = 3), and basic research (n = 1). Conclusion: This bibliometric study provides valuable insights into the global development of ARM research, and shows that clinical studies and international collaborations dominate in this field.